Autogenous Healing in Ultra-High-Performance Fibre Reinforced Concrete: application in two reduced scale water reservoirs - Caballero-Jorna Marta; Doostkami Hesam; Roig-Flores Marta; Serna Pedro (MATEC Web of Conferences, 2022)
Self-healing is defined as the capacity of a material to repair internal damage without any external intervention. In the case of concrete, this process can be autogenous, which is the natural capacity of the material. Ultra-High-Performance Fibre Reinforced Concrete (UHPFRC) has a high self-healing potential due to its high binder content with a low w/b ratio and its crack pattern with multiple micro cracks. This paper describes two UHPFRC water reservoirs, which were designed to minimise the volume of concrete used. The design is made of ribbed thin walls where shrinkage cracks are likely to happen. The objective of this work is to study the autogenous healing capability of this concrete in these cracks. The two water reservoirs have internal dimensions of 1.30×0.75×0.70 m³ and with 20 mm thickness in the centre of the walls. These walls displayed cracks (w < 100 μm), which were produced just after casting. Both reservoirs were filled with water, showing apparent water leakage. The cracks were monitored for 30 days, analysing pictures taken with an optical microscope. The results show that UHPFRC is able to heal autogenously under the conditions in this work, recovering completely the water tightness required for the water reservoirs.